2016
DOI: 10.1016/j.niox.2016.04.007
|View full text |Cite
|
Sign up to set email alerts
|

Regulating the nitrite reductase activity of myoglobin by redesigning the heme active center

Abstract: Heme proteins perform diverse functions in living systems, of which nitrite reductase (NIR) activity receives much attention recently. In this study, to better understand the structural elements responsible for the NIR activity, we used myoglobin (Mb) as a model heme protein and redesigned the heme active center, by introducing one or two distal histidines, and by creating a channel to the heme center with removal of the native distal His64 gate (His to Ala mutation). UV-Vis kinetic studies, combined with EPR … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 58 publications
1
21
0
Order By: Relevance
“…14a), with the activity of mesoMb ~3.4-fold that of WT Mb. On the other hand, Lin and coworkers [135] found that the NIR activity of Mb can be regulated by redesign of the heme active center instead of modifying the heme group. By studying a series of Mb distal histidine mutants and the channel mutants, it showed that an enhancement of NIR activity was achieved by creation of a water channel to the heme center (H64A mutation) and relocation of the distal histidine (F43H mutation) (Fig.…”
Section: Heme Analogsmentioning
confidence: 99%
See 1 more Smart Citation
“…14a), with the activity of mesoMb ~3.4-fold that of WT Mb. On the other hand, Lin and coworkers [135] found that the NIR activity of Mb can be regulated by redesign of the heme active center instead of modifying the heme group. By studying a series of Mb distal histidine mutants and the channel mutants, it showed that an enhancement of NIR activity was achieved by creation of a water channel to the heme center (H64A mutation) and relocation of the distal histidine (F43H mutation) (Fig.…”
Section: Heme Analogsmentioning
confidence: 99%
“…Copyright 2016 Elsevier; (b) Relative reactivities of Mb distal histidine mutants and the channel mutants with respect to that of WT Mb. The X-ray structure of met F43H/H64A Mb was shown for clarification[135].…”
mentioning
confidence: 99%
“…Various fungi, including A. muscaria,a lso contribute to the nitrogen cycle with nitrite as possible metabolic substrate. Additionally,r ational design based on metallobiomolecules [62][63][64] hasb een employed for as imilar purpose. [21] Despite such great importance,t he chemical homogeneous reduction of nitrites by inorganic transition metals and internal transition-metal compounds has rarely been investigated.M ost studies focusedo ni ron [33][34][35][36][37][38][39][40][41][42][43][44][45] or copper [46][47][48][49][50][51][52] complexes that mimicked nitrite reductases.H owever,N O 2 À reduction with Ru, [53] Mo, [54][55][56] Ti,C r, [56] Co [57][58][59] andU [60] was also reported.…”
Section: Introductionmentioning
confidence: 99%
“…In a related study, Lin, Tan, and co-workers created a channel to the heme pocket of Mb by removing distal His64, a gate for O2 binding, and introducing a distal histidine at position 43 (F43H/H64A) [103]. A unique water channel was formed between the heme pocket and the solvent by successive H-bonding interactions of water molecules (W1-W7) in F43H/H64A Mb (Fig.…”
Section: By Introducing An Additional His At Position 43 In the Distamentioning
confidence: 99%